METHODS OF TEACHING BIOLOGY - Kurbanova Ulashoy Bazarovna (International Engineering Journal For Research & Development, 2022)
This article describes the methods of teaching biology, the content of biological sciences, the development of the content, forms, means and methods of teaching sciences that help them to develop as a fully developed person, to provide in-depth knowledge of biological sciences.